Surveillance of multi-drug resistant pathogens in two Romanian university hospitals - Licker, Monica; Baditoiu, Luminita; Muntean, Delia; Dragomirescu, Liliana; Horhat, Florin; Piluţ, Ciprian; Hogea, Elena; Deutsch, Petru; Adam, Angela; Moldovan, Roxana (International Journal of Infection Control, 2012)
Hospital acquired infections and bacterial multi-drug resistance (MDR) involve high costs, difficult to manage in medical systems with limited resources. This study, part of the PNCDII 42121/2008 national research project, proposed the investigation of multidrug-resistant bacteria prevalence, concurrent with costs evaluation in two intensive care units (ICUs) from Timisoara university hospitals: Emergency Clinical County Hospital (ECCH) and Institute of Cardiovascular Diseases (ICD). During January-October 2010, we performed a surveillance focused on the following major exponents: Meticillin-resistant Staphylococcus aureus (MRSA), extended spectrum beta-lactamase (ESBL) producing enterobacteria and carbapenem-resistant non-fermentative Gram negative bacilli, with duplicates and colonisation germs exclusion. Selected germs identification and phenotyping were performed with the help of automatic VITEK 2 compact system, using VITEK 2 GP/GN identification cards and AST cards for antimicrobial sensitivity tests. We also performed Hodge tests for ESBL producing carbapenem resistant enterobacteria. At ECCH we isolated 534 bacterial strains, with a 35,44% prevalence for MRSA, 37,32% ESBL enterobacteria and 43,94% carbapenem-resistant nonfermenters. From 73 strains isolated from ICD, the MRSA prevalence was 8,00%, respectively 23,33% ESBL enterobacteria and 11,11% carbapenem-resistant non-fermentatives. The average number of antimicrobial treatment days/MDR infectious episode was 9.11days in ECCH/29.57days in ICD, with an average hospitalisation cost of 3,657.35 €/patient in ECCH/3,780.87 €/patient in ICD. As a conclusion, the study established high prevalence rates of Gram negative bacteria, especially of carbapenem-resistant nonfermenters and evaluated the burden produced on our sanitary sistem, by infections with MDR bacteria.